Autoimmune hepatitis: From current knowledge and clinical practice to future research agenda. (18th May 2017) - Sebode, Marcial; Hartl, Johannes; Vergani, Diego; Lohse, Ansgar W.; ,
Abstract: Autoimmune hepatitis is a chronic inflammatory liver disease. Unknown triggers lead to a mainly T cell‐mediated immune response targeting the liver, the main auto‐antigen of which has not been identified yet. The diagnosis of autoimmune hepatitis is based on the elevation of immunoglobulin G/hypergammaglobulinemia, detection of characteristic autoantibodies as well as a typical pattern on liver histology. Exclusion of other causes of hepatitis and response to immunosuppressive treatment support the diagnosis of autoimmune hepatitis. The mainstay of autoimmune hepatitis treatment has, from its first description to the current time, consisted of predniso(lo)ne to induce remission, in combination with azathioprine, which is used to maintain it. Nonetheless, side effects and non‐response with ongoing inflammation despite standard therapy demand treatment alternatives. Only through a better understanding of the pathogenesis of autoimmune hepatitis can a more selective and effective treatment be offered to patients in the future. Until this goal is reached, improvement of diagnostic approaches and optimization of current therapy rank highest on the research agenda for autoimmune hepatitis.